2013
DOI: 10.2337/db13-0508
|View full text |Cite
|
Sign up to set email alerts
|

Elastin-Derived Peptides Are New Regulators of Insulin Resistance Development in Mice

Abstract: Although it has long been established that the extracellular matrix acts as a mechanical support, its degradation products, which mainly accumulate during aging, have also been demonstrated to play an important role in cell physiology and the development of cardiovascular and metabolic diseases. In the current study, we show that elastin-derived peptides (EDPs) may be involved in the development of insulin resistance (IRES) in mice. In chow-fed mice, acute or chronic intravenous injections of EDPs induced hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
122
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 98 publications
(127 citation statements)
references
References 41 publications
3
122
0
2
Order By: Relevance
“…9,10 In addition to this structural role, elastin-derived peptides have been shown to contribute to insulin resistance by blocking glucose uptake in muscle and adipose tissue. 11 The degradation of the ECM proteins such as collagen and elastin is controlled by proteinases that include matrix metalloproteinases (MMPs) and their endogenous inhibitors such as tissue inhibitors of metalloproteinases (TIMPs). [12][13][14] Of these, MMP-12 is a metalloelastase that has the capacity to degrade elastin and plays important roles in tissue fibrosis and injury.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 In addition to this structural role, elastin-derived peptides have been shown to contribute to insulin resistance by blocking glucose uptake in muscle and adipose tissue. 11 The degradation of the ECM proteins such as collagen and elastin is controlled by proteinases that include matrix metalloproteinases (MMPs) and their endogenous inhibitors such as tissue inhibitors of metalloproteinases (TIMPs). [12][13][14] Of these, MMP-12 is a metalloelastase that has the capacity to degrade elastin and plays important roles in tissue fibrosis and injury.…”
Section: Introductionmentioning
confidence: 99%
“…29,30 Indeed, ≈29 different peptides were identified in kE mixtures by mass spectrometry analysis with one third containing the bioactive GxxPG motif (not shown). 14 In contrast, the scrambled VVGPGA is unable to adopt the type VIII β-turn conformation because of the lack of GxxPG motif. 30 However, previous studies have reported that simple proline-containing peptides, such as PG, WP, and PGP (putative fragments of collagen and elastin), possess significant antithrombotic and anticoagulant effects in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…These 3 subunits form a functional receptor in human platelets that is able to trigger an increase in sialidase activity on binding to EDP. In contrast to PPCA, the catalytic activity of Neu-1 has been shown to be essential for ERC-mediated effects both in vitro 19,32 and in vivo 13,14 by catalyzing the local conversion of GM 3 ganglioside into lactosylceramide. 19,32 Expression of Neu-1 and PPCA has been already reported in platelets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations